Transformative action towards regenerative food systems: a large-scale case study - Buckton, Sam J.; Fazey, Ioan; Doherty, Bob; Bryant, Maria; Banwart, Steven A.; Carmen, Esther; Connolly, Annie; Denby, Katherine; Kendrick, Ian; Sharpe, Bill; Wade, Ruth N.; Ball, Peter; et al. (Public Library of Science (PLoS), 2024)
We urgently need to foster regenerative food systems that mutually reinforce human and ecological health. However, we have limited understanding of the action pathways that could encourage the emergence of such systems. Here we report on an extensive Three Horizons futures process, conducted with diverse participation from food system researchers and practitioners, to identify core domains of action for transforming the food system of Yorkshire, UK, towards a regenerative future. After establishing the contrast between the current degenerative and envisioned future regenerative food system, six core action domains were identified that require support to enable transformation: 1) enhancing supply chain connectivity and innovation to support diverse hybrid business ecosystems; 2) scaling environmentally beneficial and regenerative farming; 3) empowering citizens to reshape food demand; 4) providing trusted, accessible knowledge support for standards and incentives; 5) supporting schools and young people as drivers of long-term change; and 6) ensuring coordination and mutual support across domains. Our results highlight the importance of efforts to cohere synergic action, ambitious visioning, and addressing issues of power. Overall, our study sets an ambitious standard for co-developing action priorities to encourage regenerative futures.
More detailed Three Horizons results can be found in FixOurFood’s freely accessible subsystem reports [74–76]. Original material (post-it notes etc.) is stored on a number of murals in FixOurFood’s Mural (https://www.mural.co/) account. Data are available from fixourfood@york.ac.uk or the University of York Open Research team (lib-open-research@york.ac.uk ) for researchers who meet the criteria for access to confidential data.
Keywords: 35 Commerce, Management, Tourism and Services; 4410 Sociology; 44 Human Society; Generic health relevance; 2 Zero Hunger